Identification of the determinants of incomplete vaccination in Australian children. (11th April 2019) - Lim, Christopher; Currie, Grace E.; Waddington, Claire S.; Wu, Yue; Setijo, Sharon; Leask, Julie; Marsh, Julie A.; Snelling, Thomas L.
Highlights: Demographic/social factors, vaccine beliefs, and vaccination status were captured. Most parents are supportive of vaccination. Many parents incorrectly reported their child as fully vaccinated. Incomplete vaccination was associated with demographic and socio-economic factors. Abstract: Background and aims: We aimed to understand the risk factors associated with incomplete vaccination, which may help to identify and prioritise opportunities to intervene. Methods: Consenting parents of children <6 years old attending an outpatient clinic completed a questionnaire, which captured demographic information and their level of agreement with belief statements about vaccination using a 7-point Likert scale. Vaccination status was determined from the Australian Childhood Immunisation Register and deemed either "complete" (no doses overdue) or "incomplete" (1 or more doses overdue) at the time of questionnaire completion. Results: Of 589 children of respondents, 116 (20%) had an incomplete vaccination status. Of these, nearly two-thirds (63%) of parents believed that their child was, in fact, fully-vaccinated. Compared to those with a complete vaccine status, children with an incomplete vaccine status were more likely to be born overseas (p < 0.001), have a larger family size (p = 0.02) and to have parents with lower educational attainment (p = 0.001). Parents of children with an incomplete status reported more doubt about the importance of vaccination and greater concern about vaccine safety, compared to parents of children with a complete status. Conclusion: Most parents are supportive of vaccination. Sociodemographic factors may contribute more to the risk of incomplete vaccination than attitudes or beliefs. Some parents are unaware of their child's vaccination status, suggesting that simple and modern reminders may assist parents to keep up to date.